In vivo study on the effect of noni leaf extract cream (Morinda Citrifolia L) on PDGF and TNF-α levels in cut wounds - Sari, Shintia Devi Arum; Mulyani, Sri Priyantini; Putra, Agung; Setiawan , Eko (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
ABSTRACT Background: Skin wounds damage the structure and epithelial tissue, resulting in scar tissue formation. Prolonged wound healing or excessive body response will inhibit the normal process and produce unaesthetic scar tissue. Many plant extracts and their active components can accelerate the wound healing process, Noni leaf extract has antioxidant activity and accelerates wound healing. Objective: This study aims to determine the effect of noni leaf extract cream (Morinda Citrifolia L) on TNF-α and PDGF levels in Wistar rats with incised wounds. Method: A laboratory experimental study with a post-test only control group design. Consisting of five treatment groups, namely the healthy rat group (KS), Negative group (KN) rats with incised wounds without treatment, positive group (KP) rats with incised wounds that were smeared with povidone-iodine cream, treatment group 1 (P1) rats that were smeared with 20% noni leaf extract cream, and treatment group 2 (P2) rats that were smeared with 40% noni leaf extract cream, treatment for 3 days then examined the levels of TNF-α and PDGF skin tissue using the ELISA method. Results: The average TNF-α levels showed a significant difference between groups p of 0.000 (p <0.05) with the One way anova test, the highest average in group (KN) 220.68 pg / mL, there was a decrease in all treatment groups with the lowest TNF-α levels in group (KP) 76.59 pg / mL. The average results of TNF-α levels showed a significant difference of p 0.000 (<0.05) with the One-way ANOVA test, the group without intervention (KP) had the lowest PDGF levels while the group (P2) experienced the highest increase in PDGF levels. Conclusion: Administration of noni leaf extract cream with doses of 20% and 40% had an effect on reducing TNF-α levels and increasing PDGF levels in Wistar rats with incised wounds.